Pulmonary commitment post contagious by COVID-19: radiological perspective by images (Research, Society and Development, 2022)
At the end of 2019, they identified a new strain of Coronaviridae, similar to epidemics of previous respiratory infections, as well as containing individuals who test positive, but do not show any symptoms, however it is possible that transmission is made. COVID-19 can manifest as a simple flu or in some more serious cases serious respiratory complications can occur, and in older patients and with chronic diseases. Transmission can be caused by droplets expelled through sneezing and coughing or by contaminated surfaces. The diagnosis can be made through the nasal route, using the RT-PCR method. Imaging procedures are very important tools to assist in the treatment and prognosis of SARS-COV-2. The methodologies of Chest X-ray and Computed Tomography contain cheaper means, with high sensitivity to enable examinations in ICU patients and in triage. Therefore, this integrative literature review thesis was based on pulmonary involvement and medical imaging means for assistance in the initial and evolutionary phase of COVID-19 infection, generating greater demand for these procedures and arousing even more interest in the virus. and methods for diagnosis. However, the work had 28 articles identified on digital and printed platforms by magazines and more recent books, which collaborated to highlight the diagnoses discovered with the contribution of imaging media and help for future studies.